Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Sintiani Jerahu; Yusram Adi; Andi Herman Tellu (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to determine whether CR, DER, and ROA affect changes in profit. The data obtained using the quantitative descriptive method with the criteria (1) Consumer Goods Industry Companies listed on the Indonesia Stock Exchange and consistently exist during the 2019-2023 research period, (2) Consumer Goods Industry Companies that provide financial report data during the 2019-2023 research period and consumer goods industry companies do not generate negative profits. The results of the analysis show that the data used in this study meet the classical assumptions, which include: no symptoms of multicollinearity, autocorrelation, no symptoms of heteroscedasticity, and normally distributed data. From the results of the regression analysis shows that the most influential on the independent variable of profit growth is the profitability ratio. With the results shown that the profitability ratio has a positive and significant effect on profit growth.